THE GLYCERIDES STRUCTURE OF Cn'Ruu.us COLOCYNTHIS - Javed, M A; Kausar, T; Saleem, M; Khan, G R (Biological Sciences - PJSIR, 2003)
The tnacylgl)'ccrol s separated from Ci1r11//11.r colocy111his seed oil "ere fruclionnlcd b} silver nitrate impregnated thin layer chromatograph) 11110 si:-. fractions ,,1th respect lo their degree of unsalurntion. Th.: composition and nature of the l'auy acids at their 1.3- and 2-positions "ere determined b) the use of pnncreatic lipase and gas chromatography The unsaturated C18 acids occup) the 2-position depending upon thc comparatm:1' higher percentage of the respective acid.